VD_FINDINFO Jug / 2025 / 225 vom 16. Juli 2024 - VD Tribunal cantonal (2024)
FRAIS JUDICIAIRES, AVOCAT, INDEMNITÉEN GÉNÉRAL, DOL PRINCIPAL, PAIEMENT, PRIX | 211 al. 1 CO, 28 CO, 426 al. 2 CPP (CH), 430 al. 1 let. a CPP (CH)